Negotiating a coach identity: a theoretical critique of elite athletes' transitions into post-athletic high-performance coaching roles. Issue 6 (24th July 2021) - Blackett, A. D.; Evans, A. B.; Piggott, D.
ABSTRACT: There has been a growing trend of elite athletes being fast-tracked into post-athletic high-performance coaching roles in association football and rugby union in England and Wales. This has been facilitated by an increase in bespoke and condensed formal coach education courses that are designed to accelerate current and/or former elite athletes in attaining their coaching accreditation. Hitherto, however, the individual lived experiences of former athletes on this career trajectory during their transition to coaching remains under-investigated. The purpose of this study, therefore, was to analyse how elite male association football and rugby union athletes based in England and Wales (re)created, re-negotiated or transformed their identities when negotiating a fast-tracked career pathway into a post-athletic high-performance coaching role. Fifteen male rugby union ( n = 10) and association football ( n = 5) athletes were interviewed on two separate occasions over twelve months. Interviews coincided with the start and end dates of the level three coach education course which they were concurrently enrolled on. Interviews focused upon how they (re)created their professional identities upon negotiating the career transition into a post-athletic high-performance coaching role. Data were critically theorised against sociological concepts associated with the theoretical frameworks of Bourdieu, Goffman and Foucault. Results identified how the development of a coaching identity was articulated through the need to define a 'coaching philosophy'. Upholding a coach identity in an 'honest' disposition so athlete to coach respect could be best attained was expressed by all participants and contrasted with Goffman's concepts of front and backstage impression management. Self-reflexive practices of Foucault's askesis were engaged to varying levels to create a coach identity. In three cases this resulted in participants' contestation of their respective club's identity/culture and losing employment as a coach. Finally, recommendations on how coach education structures can further support these coaches in their career transitions are made.